PENGARUH KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN ASING TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN YANG LISTING DI BEI SEKTOR MANUFAKTUR PERIODE 2013-2015 - Kiki Mega Santi; Makhdalena Makhdalena; RM. Riadi RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aimed to investigate the effect of managerial ownership and foreign ownership of the firm value. The population in this study are all manufacturing companies listed in the Indonesian Stock Exchange that have data (managerial ownership, foreign ownership and firm value) consecutive years (2013 until 2015). The data obtained from Indonesian Capital Market Directory (ICMD) researched each company. The data analysis technique used in this research is multiple linear regression. These results indicate that managerial ownership and foreign ownership simultaneously affect the firm value. While partially, managerial ownership and foreign ownership negatively affect firm value.Keywords: Managerial ownership, Foreign ownership, Firm Value